Generation of two human iPSC lines from patients with maturity-onset diabetes of the young type 2 (MODY2) and permanent neonatal diabetes due to mutations in the GCK gene - Yasmin W. Abu Aqel (17100289) (2020)
Heterozygous and homozygous mutations in the glucokinase (GCK) gene leads to maturity-onset diabetes of the young type 2 (MODY2) and permanent neonatal diabetes (PNDM), respectively. Here, we report the generation of two induced pluripotent stem cell (iPSC) lines, QBRIi010-A and QBRIi011-A, from patients with MODY2 and PNDM due to mutations in the GCK gene (c.437 T > C). The generated iPSC lines displayed pluripotency characteristics, were able to differentiate into the three germ layers, and showed normal karyotypes. These iPSC lines will serve as valuable human cell models for understanding diabetes pathogenesis and developing new therpaies for diabetes. Other Information Published in: Stem Cell Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.scr.2020.101991